2016
DOI: 10.1177/1094428116658958
|View full text |Cite
|
Sign up to set email alerts
|

Review and Recommendations for Integrating Mediation and Moderation

Abstract: Usage of models integrating mediation and moderation is on the rise in the organizational sciences. While moderation and mediation are fairly well understood by themselves, additional complexities emerge when combining them. Some guidance exists regarding the empirical testing of such models, but this guidance is widely misunderstood. Furthermore, very little guidance exists regarding the theoretical justification of such models. This article offers a checklist of recommendations for the presentation, justific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 119 publications
(100 reference statements)
1
71
1
1
Order By: Relevance
“…First, it has been recommended by Holland et al. () to examine the specific pathway of the mediation model which would be moderated by gender. Therefore, hierarchical regression analysis was used to test whether gender specifically moderated the effect of prenatal risk on inhibitory control (path a) or the effect of inhibitory control on physical aggression (path b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it has been recommended by Holland et al. () to examine the specific pathway of the mediation model which would be moderated by gender. Therefore, hierarchical regression analysis was used to test whether gender specifically moderated the effect of prenatal risk on inhibitory control (path a) or the effect of inhibitory control on physical aggression (path b).…”
Section: Methodsmentioning
confidence: 99%
“…Age of the children at the data waves was also examined as potential covariate. The moderated mediation model was tested following the recommendations of Hayes (2015) and Holland, Shore, and Cortina (2017). The first hypothesis was tested using regression analysis to examine whether prenatal risk predicted children's physical aggression.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, we first framed a series of hypotheses on individual linkages in a sequence to explore independent and direct associations. We then integrated mediation and moderation (). We assumed partial mediation via sleep quality and quantity, as other mediators of the relationship between food insecurity and obesity have been established ().…”
Section: Introductionmentioning
confidence: 99%
“…All of the models discussed in Edwards and Lambert (2007) share the same X->M->Y core but vary in the location of the moderation. Holland et al (2017) found that the most common is the first stage (X->M) moderation model. Consider as an example a portion of the model presented in Zhang and Bartol (2010).…”
Section: Conditional Indirect Effects Containing Rv Interactions Conmentioning
confidence: 99%